A Study of Non-Finite Forms of Anaphoric do in the Spoken BNC - Kimberly Oger (Anglophonia)
“British do” (sometimes referred to as “propredicate” or “substitute” do) is a non-finite form of intransitive do, used as an anaphor in conversational British English. It is rarely used in other varieties of English, and American speakers, in particular, tend to consider its usage ungrammatical. British do has received very little attention in the literature, particularly in comparison with other anaphoric phenomena involving do, such as ellipsis. What has been written has been mainly descriptive in nature and based on contrived or literary examples. No in-depth analysis has been carried out on a corpus based on real data that is representative of English usage. In this article I present the first study based on empirical data, i.e. 486 occurrences of British do taken from the spoken BNC. I also discuss the initial results of this study, which tend to disprove much of what has heretofore been written on the subject, and raise further questions to be addressed.